Study of Photobleaching of Organic Laser Dyes in Solid Materials: Enhancing Photostability of Organic Laser Dyes in Solid Polymer Matrices (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A technique is described for easuring the rate of photobleaching of organic laser dye molecules in solid polymer matrices. For solid arrangements of rhodamine 6 G (Rh6 G) in appropriate copolymer details of 2-hydroxyethyl methacrylate (HEMA) and methyl methacrylate (MMA), lasing efficiencies like those found in ethanolic arrangement and improved photochemical solidness contrasted and those obtained in past polymeric materials were illustrated.